Gamelan Gamelan sebagai cermin identitas budaya: gamelan - Septian Trijayanto; Karsiwan; Lisa Retno Sari (PANGGUNG, 2025)
Gamelan has a strong social and spiritual function, strengthening solidarity and reflecting the traditional values of society. The purpose of this study is to determine the function of gamelan as a cultural identity of the Javanese community in Palas Subdistrict, South Lampung Regency. The type of research used is descriptive qualitative, with data collection using in-depth interviews, observation and documentation techniques. Data analysis utilised qualitative data analysis with stages of data collection, data reduction, and conclusion drawing. The results of the study illustrate that gamelan acts as a social medium that connects generations and strengthens community social bonds. Gamelan also functions as a spiritual symbol in various traditional ceremonies and religious rituals, creating harmony and balance in the cultural identity of its owners. The local community in the Palas area plays a role through art associations by continuing to strive to preserve the gamelan tradition in a sustainable manner. In addition, efforts to preserve and pass on traditional arts and culture can be carried out in various ways, such as integrating gamelan as part of performing arts into the education curriculum through cultural arts lessons and local content, as well as holding festivals or regional cultural events so that gamelan continues to have a stage in accompanying traditional music and other performances.